Illustrations of the IPA: Russian - Yanushevskaya, Irena (My University, 2015)
Russian (ISO 639-3 rus) is an Indo-European East Slavic language spoken by about 162 million people as their first language and about another 110 million as their second language (Lewis, Simons & Fennig 2013), mainly in the Russian Federation (where it is the native language of about 80% of the population, see Berger 1998, Federal’naja služba gosudarstvennoj statistiki (Federal State Statistics Service) 2012: 228–232) and in the other former republics of the USSR (among which it is co-official in Belarus, Kazakhstan and Kyrgyzstan). Large groups of Russian speakers (so-called heritage speakers) also live in Europe (especially Germany: almost 3 million or 3.5% of the population, Brehmer 2007: 166–167), Israel (about 1 million or 20%, Glöckner 2008) and the United States (850,000 or 0.3%, Shin & Kominski 2010: 6).
PUBLISHED
Keywords: LINGUISTICS; Phonetics; Russian language